Rights of landowners under the National Land Code 1965 / Fahim Hamam, Marisha Dianah Md Darus and Saiful Aidil Muliani Mustapah - Hamam, Fahim; Md Darus, Marisha Dianah; Mustapah, Saiful Aidil Muliani (2014)
This research project is about the studies on the rights of landowners as provided in the National Land Code 1965. We will go through from the historical part of land ownership where there was no formal law enacted until the establishment of the Torrens System and the National Land Code 1965. Earlier in Peninsular, before the adoption of the Torrens System, the land law was basically based on Malay custom and Islamic law. The introduction of Torrens title or the system of titles and interests by registration into this country resulted in the passing of the NLC. Therefore, through the research finding, we will see how the land law in Malaysia has been developed. By conducting this research, we found that there are a lot of landowners' rights provided under the National Land Code 1965 and we hope that the landowners will be aware of the rights provided for them. After collecting, analysing and justifying all the finding based on the opinion and reliable facts and sources, we come to a conclusion that there are a lot of landowners' rights mentioned and discussed in the National Land Code 1965. The land owners somehow or rather are protected and covered by the rights for them and their properties to make sure that no person is being cheated or treated unjustly and unfairly.